2015
DOI: 10.17221/8169-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Fermented liquid feed for weaned piglets: impact of sedimentation in the feed slurry on performance and gut parameters

Abstract: ABSTRACT:In two experiments with weaned piglets, the effects of fermented liquid feed (FLF) (produced with probiotic strain Pediococcus acidilactici, Bactocell ® , Lallemand S.A.S.) on performance and some bacteriological and morpho-histological parameters of the gut were investigated, and the impact of sedimentation of the solids in the FLF thereon. In experiment I, FLF or the same dry feed (DRY) was offered ad libitum for 28 days to two groups of 15 weaned piglets (28 days of age) each (3 replicates of 5 pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
3
9
0
1
Order By: Relevance
“…In a review on FLF for pigs, Missotten et al (2010) reported that FLF containing 36 000 mg lactic acid/kg DM can have a beneficial effect on feed intake, daily gain and feed to gain ratio. Very recently, the same beneficial effects were observed in a 28-day feeding trial with piglets (27-28 days old, 6.3-7.9 kg body weight) fed FLF, containing lactic acid in the range of 55 000-125 000 mg/kg DM (Missotten et al, 2015).…”
Section: Safety For Pigssupporting
confidence: 55%
“…In a review on FLF for pigs, Missotten et al (2010) reported that FLF containing 36 000 mg lactic acid/kg DM can have a beneficial effect on feed intake, daily gain and feed to gain ratio. Very recently, the same beneficial effects were observed in a 28-day feeding trial with piglets (27-28 days old, 6.3-7.9 kg body weight) fed FLF, containing lactic acid in the range of 55 000-125 000 mg/kg DM (Missotten et al, 2015).…”
Section: Safety For Pigssupporting
confidence: 55%
“…In the present study, the addition of FTR to the diet increased the VH and ratio of villi height to the crypt depth of the duodenum, jejunum, and ileumm and reduced the CD of the duodenum and jejunum, which was basically consistent with the results of previous studies. Missotten et al [48] found that fermented feed could significantly increase the VH of the intestine, increase the surface area of the small intestine, and enhance the digestion and absorption of nutrients. Similar findings have been reported in the studies of Choi et al [49], who demonstrated that adding fermented products to a piglet diet could increase the VH of duodenum, jejunum, and ileum, but that it did not significantly affect the CD.…”
Section: Intestinal Morphologymentioning
confidence: 99%
“…Considering today's reduction in the weaning time of piglets (Niekamp et al 2007;Smith et al 2010;Xiao et al 2014) and its effect on the animals' underdeveloped immune and digestive systems, probiotic fermented feed additives have been gradually included in piglet feeding practices. These additives are safe, non-toxic and efficient; therefore, they have become a popular topic of discussion and study among animal nutritionists (Le et al 2016;Missotten et al 2016;) Among them, fermented lactic acid bacteria feed has been the most widely used in recent years (Missotten et al 2009;Lin et al 2010). However, researchers have found that piglets weaned using a large amount of fermented lactic acid bacteria feed were prone to diarrhoea.…”
Section: Introductionmentioning
confidence: 99%